Formal specification of a wall-climbing robot using Z-A case study of small-scale embedded hard real-time system - Mohamad, Radziah; Abang Jawawi, Dayang Norhayati; Deris, Safaai; Mamat, Rosbi (Penerbit UTM Press, 2001)
The task of checking whether a real-time system satisfies its timing and concurrency specifications is extremely important. One major area of research addressing software reliability aspect is called formal method, which attempts to prove the correctness of programs with respect to system specifications. Since, timing and concurrency properties can be very important in the operation of real-time systems, there is a need for applying formal methods to verify timing properties. This paper investigates the process of building a formal specification of a small-scale embedded hard real-time systems using Z. It is expected that the formal specification presented in this paper can provide assistance in analysing design trade-offs early in the development process. It is also expected that this paper can act as the foundation for any upcoming formal methods related project especially for small-scale real-time systems project.